Contribution of Industrial Engineering in World Development (Ingeniería, Sostenibilidad y Sociedad, 2023)
The objective of this article, which is to propose a study by showing the systematic perspective of the industrial engineer for decision-making derived from the new managerial role in the face of environmental challenges and the various orientations for the perception of problems in the world, with choices of alternatives and optimization of results. There are various orientations to focus on the company, which are oriented towards a partial aspect, proposing incomplete solutions due to a biased definition of the problem. These are structure, process, person and moment, the first includes techniques that lead to optimal results, the second considers functionality, includes the classics, neoclassics, strategic process, the third considers human relations, behavior, knowledge management, the last one includes change, organizational development, evolution and technological innovation, contingency and strategy.
Keywords: industry; innovation; logistics; production; planning; engineering; world class competitiveness